Application Of Potassium Fertilizer And Organic Fertilizer For Rabbits On The Growth And Years Of Okra (Albemoschus Esculentus L) - Mukhtar Yusuf; Fitria Fitria; Risnawati Risnawati; Rini Susanti; M Alqamari; Hadriman Khair; Alridiwirsah Alridiwirsah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
Okra (Albemoschus esculentus L) is a fruit-shaped vegetable crop and is a potential crop because it has business opportunities. Okra production is still low and has not been able to meet the needs of one of the problems, namely inappropriate fertilization. It is necessary to conduct research that aims to determine the effect of Potassium fertilizer and organic rabbit fertilizer on the growth and yield of okra. The research location is in Sampali Village, Percut Sei Tuan District, DeliSerdang Regency, North Sumatra Province. When the research was carried out in February-May 2021, the materials used were okra seeds, potash fertilizer and rabbit manure. The research method used a factorial Randomized Block Design (RBD) with two treatments and three replications of Potassium (K), namely: K0: without K fertilizer, K1: 5 g/plot, K2: 7.5 g/plot, K3: 15 g/plot while rabbit organic fertilizer (P), namely: P0: without rabbit organic fertilizer, P1: 1 kg/plot, P2: 1.5 kg/plot, P3: 2 kg/plot. The results showed that for observation the number of fruits per plant had no significant effect but gave the best results on Potassium 15 g/plot and organic fertilizer for rabbits P3: 2 kg/plot while Potassium fertilizer had a significant effect on stem diameter and flowering age while organic fertilizer for rabbits had a significant effect on plant height this is because Potassium fertilizer functions to strengthen stems, physiological processes, formation of flowers and fruit. While rabbit organic fertilizer contains nitrogen which plays a role in the vegetative phase for plant growth.